Winners and Losers from Regional Integration Agreements. - Venables, A (2003)
How are the benefits and costs of a customs union divided between member countries? Outcomes depend on the comparative advantage of members, relative to each other and relative to the rest of the world. Countries with a comparative advantage between that of their partners and the rest of the world do better than countries with an "extreme" comparative advantage. Consequently, integration between low income countries tends to lead to divergence of member country incomes, while agreements between high income countries cause convergence. Results suggest that developing countries are likely to be better served by "north-south" than by "south-south" agreements.